Romance Rewritten The Evolution of Middle English Romance. A Tribute to Helen Cooper - Archibald, Elizabeth; Leitch, Megan; Saunders, Corinne (Studies in Medieval Romance, 2018)
Literature; European and World Literature: General Interest